Studi Literatur: Peran Motivasi dalam Proses Belajar Mengajar - Idyana Adha; Neviyarni; Herman Nirwana (Citra Dharma Cindekia, 2022)
Motivation plays an important role in the learning process. If teachers and parents can provide good motivation to students or their children and then in students or children there will be encouragement and desire to learn better. Providing good and appropriate motivation, then the child can realize the benefits of learning and the goals to be achieved by learning. Learning motivation is also expected to be able to arouse enthusiasm for learning, especially for students who are lazy to study as a result of negative influences from outside the students. Furthermore, it can form the habit of students being happy in learning so that their learning achievement can increase. As a counselor or teacher increasing student motivation in learning is explaining learning objectives to students, giving gifts, praise, punishment, generating encouragement for students to keep learning, forming good study habits, helping students with learning difficulties individually and in groups using varied methods, good media and in accordance with learning objectives. The method used is literature study, which is a type of research based on reading. The purpose of a literature study is to gather as much information as possible about a particular topic or issue.